A social cost-benefit analysis of meat taxation and a fruit and vegetables subsidy for a healthy and sustainable food consumption in the Netherlands - Marlin J. Broeks; Sander Biesbroek; Eelco A. B. Over; Paul F. van Gils; Ido Toxopeus; Marja H. Beukers; Elisabeth H. M. Temme (BMC, 2020)
Abstract Background Implementation of food taxes or subsidies may promote healthier and a more sustainable diet in a society. This study estimates the effects of a tax (15% or 30%) on meat and a subsidy (10%) on fruit and vegetables (F&V) consumption in the Netherlands using a social cost-benefit analysis with a 30-year time horizon. Methods Calculations with the representative Dutch National Food Consumption Survey (2012-2014) served as the reference. Price elasticities were applied to calculate changes in consumption and consumer surplus. Future food consumption and health effects were estimated using the DYNAMO-HIA model and environmental impacts were estimated using Life Cycle Analysis. The time horizon of all calculations is 30 year. All effects were monetarized and discounted to 2018 euros. Results Over 30-years, a 15% or 30% meat tax or 10% F&V subsidy could result in reduced healthcare costs, increased quality of life, and higher productivity levels. Benefits to the environment of a meat tax are an estimated €3400 million or €6300 million in the 15% or 30% scenario respectively, whereas the increased F&V consumption could result in €100 million costs for the environment. While consumers benefit from a subsidy, a consumer surplus of €10,000 million, the tax scenarios demonstrate large experienced costs of respectively €21,000 and €41,000 million. Overall, a 15% or 30% price increase in meat could lead to a net benefit for society between €3100-7400 million or €4100-12,300 million over 30 years respectively. A 10% F&V subsidy could lead to a net benefit to society of €1800-3300 million. Sensitivity analyses did not change the main findings. Conclusions The studied meat taxes and F&V subsidy showed net total welfare benefits for the Dutch society over a 30-year time horizon.